P‐16.2: A Research on Gray Grid Mura for Out‐cell Metal Mesh OLED Touch Module. (26th August 2021) - Xu, Wenjie; Guo, Zongjie; Xie, Xiaodong; Pang, Bin; Yu, Feifei; He, Min
Abstract : In this paper, gray grid mura in out‐cell metal mesh touch module laminated with OLED display was analyzed. Gray grid mura could be obviously cognitive at pure white/green/red pictures, and metal mesh were shading lighting green/red/blue subpixels randomly. It's worth noted that nothing could be observed in out‐cell metal mesh combined with same definition TFT‐LCD module. Display subpixel mesh‐shading area ratio could reach 25% for OLED while the value was only 6% 7% for LCD. Experiments were designed to explore the root cause for gray grid mura such as mesh without cross‐connecting point, different angle/space mesh solution, narrow mesh width solution, and heterogeneous subpixel‐mesh‐shading was testified to be the root cause for gray grid mura. The mechanism of gray grid mura was that non‐uniform mesh blocking ratio for adjacent pixels could lead to different gray levels in adjacent pixels. When the subpixel‐mesh‐blocking ratio surpassed a sensitive threshold as 11%, difference between adjoining area could result in macro‐mura. Homogeneous and heterogeneous pixel patterns simulating actual mesh‐blocking effect were designed further to verify the supposed mechanism. Gray grid mura was also observed in heterogeneous pixel design as expected.